Experimental research of a small-scale industrial furnace with regenerative disc-flame burners - Yitong Xie; Chaokui Qin; Shuangqian Guo; Zhiguang Chen (Case Studies in Thermal Engineering, 2023)
Regenerative combustion technology has many advantages such as fuel saving, high combustion efficiency and low emission, and it has been widely used for large-scale furnaces. However, when regenerative combustion technology is adopted for small-scale furnaces, many technical problems occur. In this paper, a small-scale regenerative furnace with heat load of 70–80 kW and primary air coefficient of 1.00–1.60 was designed. It was found that the flame shifts from bright pale blue with faint rotating streamlines to yellowish transparent without apparent streamlines and to bright and transparent eventually. When main burners work stably, the temperature inside the furnace raises rapidly at first, and then the temperature increases steadily and fluctuates periodically. The highest temperature in the furnace can reach around 1300 °C. As the reversing time increases, the temperature fluctuation becomes more dramatically and the highest temperature is higher. NOx concentrations at all measurement points are below 50 ppm. Heat transfer efficiencies of each heat retainer show an increasing trend with the rise of the number of reversions. As reversing time increases, the heat transfer efficiency shows a decreasing trend.